Tes Dianostik Two Tier untuk mengidentifikasi Miskonsepsi pada pelajaran IPAS materi Tumbuhan di SDN Sonosewu - Prastyani, Oktina Dwi; Kurniawati, Wahyu (Universitas Muhammadiyah Magelang, 2025)
Science learning in elementary school means that students can understand concepts. However, some students find it difficult to understand the concept of science learning. One of the causes of students' inability to understand concepts is when students experience misconceptions. The presentation of misconceptions on the topic